A prospective observational study on urethral catheter-associated complications among general surgical inpatients. - Kanukurthi, Dr Navyadeep; Baindla, Dr . Chandra Prakash; Sudhakar, Dr . Yerra (Student's Journal of Health Research Africa, 2025)
Background: Urethral catheterization is frequently employed in general surgical inpatients for perioperative and critical care management. However, its use is associated with a spectrum of complications, which may impact patient outcomes and prolong hospitalization. Objectives: To determine the prevalence, spectrum, and risk factors of urethral catheter-associated complications among general surgical inpatients. Methods: This prospective observational study was conducted on 100 consecutive general surgical inpatients who required urethral catheterization during hospitalization. Detailed demographic, clinical, and peri-catheterization parameters were recorded. All patients were followed for 30 days to identify catheter-related complications, including catheter-associated urinary tract infection (CAUTI), urethral trauma, blockage, and accidental dislodgement. Potential risk factors were analyzed using the chi-square test and logistic regression to determine statistical significance. Results: The mean age was 54.2 ± 15.6 years, with 62% males. Perioperative urinary monitoring was the commonest indication for catheterization (58%). The mean catheterization duration was 6.4 ± 2.8 days. Overall, 33% of patients developed at least one complication. CAUTI occurred in 14%, urethral trauma in 8%, blockage in 6%, and dislodgement in 5%. Complication rates were significantly higher in patients catheterized for >7 days (28.1% vs. 7.4%, p = 0.010), with diabetes mellitus (25.0% vs. 9.7%, p = 0.040), and with breach in aseptic technique (50.0% vs. 11.7%, p = 0.030). All complications resolved with appropriate management. Conclusions: One-third of general surgical inpatients with urethral catheters experience complications, most frequently CAUTI. Prolonged catheterization, diabetes, and aseptic breaches significantly increase risk. Recommendations: Limiting catheter duration, ensuring strict asepsis, and close monitoring of high-risk patients are essential to reduce morbidity associated with urethral catheterization.